Variations on a Theme?: comparing 4chan, 8kun, and Other chans’ Far-Right "/pol" Boards - Baele, Stéphane J. (Perspectives on terrorism, 2021)
Online forums such as 4chan and 8chan have grown in notoriety following a number of high-profile attacks conducted in 2019 by right-wing extremists who used their "/pol" boards (dedicated to "politically incorrect" discussions). Despite growing academic interest in these online spaces, little is still known about them; in particular, their similarities and differences remain to be teased out, and their respective roles in fostering a certain farright subculture need to be specified. This article therefore directly compares the content and discussion pace of six different/pol boards of "chan" forums, including some that exist solely on the dark web. We find that while these boards constitute together a particular subculture, differences in terms of both rate of traffic and content demonstrate the fragmentation of this subculture. Specifically, we show that the different/pol boards can be grouped into a three-tiered architecture based upon both at once how popular they are and how extreme their content is.